Der Beitrag der Angewandten Linguistik zur Praxisorientierung philologischer Studiengänge - Grzeszczakowska-Pawlikowska, Beata; Makowski, Jacek; Stawikowska-Marcinkowska, Agnieszka (2022)
In this article, an attempt is made to fill in the content of the higher education reform-led concepts of employability, competence and practice orientation and then to illuminate their relationship to the traditional view of the role of higher education institutions. The discussion focused on the legitimacy of practical references in teaching and learning, which was not disputed here, for example in the sense of insisting on tradition. Instead, an emphatic plea for a reflected practical orientation will be expressed.
Keywords: applied linguistics; philology; university; employability; practicability; languages for Specific Purposes; professional Communication